Motorized Vehicle Security System Using SMS with GPS Tracking Method Based on Arduino UNO - Prasetio, Andhika Dwi; Aji, Wahyu Sapto (Association for Scientific Computing Electrical and Engineering (ASCEE), 2025)
Cases of motorcycle loss are increasingly common in the community. This situation is caused by the lack of security systems installed on motorcycles, which are generally limited to the vehicle's ignition key. In fact, only a few medium-sized motorcycles are equipped with alarms as an additional form of security. A solution is needed to reduce theft or robbery on motorized vehicles, which is realized through a study entitled